Evaluasi Kesesuaian Lahan Beberapa Komoditas Tanaman Holtikultura Berbasis Sistem Informasi Geografis di Kawasan Subak Kecamatan Denpasar Barat - I KADEK ANGGA WIRA SENTANA; I NYOMAN DIBIA; NI MADE TRIGUNASIH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
Land Suitability Evaluation of Several Horticultural Crop Commodities Based on Geographic Information Systems in the Subak Area of West Denpasar This study aims to determine the actual and potential land suitability, limiting factors, assumptions of improvement efforts, making land suitability maps, and land use direction maps for vegetable and flower horticultural crops. The plants evaluated included spinach, mustard greens, eggplant, marygold, and sunflowers. This research was conducted in West Denpasar from December 2020 to March 2021. Based on the distribution of subaks in West Denpasar, there are eight subaks. The research method used survey methods to evaluate land suitability, soil analysis, and use matching methods between land quality/characteristics and plant growth requirements evaluated by Ritung et al., (2011). The results showed that the actual land suitability classes for vegetable and flower horticultural crops were classified as S1 (very suitable) to S3 (according to marginal). Land characteristics that act as limiting factors include temperature, drainage, texture, N-Total, and K2O. Improvement efforts can be made by adding fertilizers and constructing a drainage system channel, except for the limiting factor of temperature and texture, which are permanent limiting factors. The potential land suitability classes for vegetable and flower horticultural crops evaluated were S1 (very suitable) to S2 (quite suitable), with a temperature limiting factor. Based on land suitability and limiting factors for land use recommendations that can be developed in West Denpasar, namely eggplant, marygold, and sunflower, horticultural crops have more priority than spinach and greens mustard.